Milk Tea Alliance: The Power of New Democracy in ASEAN and Efforts to Increase the Effectiveness of ASEAN Norms - Imawan, Riswanda (Strata Social and Humanities Studies, 2023)
Democracy and human rights issues in the ASEAN region came into the focus of attention with the emergence of the Milk Tea Alliance, a cross-border movement fighting for democratic values. This article aims to explore the role of the milk tea alliance movement as a new democratic force in ASEAN and how it can be enhanced in effectiveness through adaptation to existing ASEAN norms and institutions. Methodologically, secondary data collection often involves the use of literature research techniques and is analyzed explanatory with the framework of constructivist analysis to understand the social construction of identity, norms, and political relations in ASEAN with the movement. This research shows that this movement effectively increases public awareness of democratic principles. Nonetheless, normative and institutional challenges in the ASEAN region require the implementation of adequate adaptive measures. The study presents several tactics aimed at increasing the influence of this movement in facilitating democratic progress in the ASEAN region.